(untitled) (CIPEEX, 2026)
Introduction: Maternal guidance is a key determinant of appropriate breastfeeding (BF) and complementary feeding (CF) practices in the first year of life. Evidence points to benefits of exclusive breastfeeding (EBF) up to 6 months and risks of early CF, but informational, cultural, and socioeconomic barriers still hinder adherence. Objective: To analyze mothers’ level of guidance/education regarding knowledge of normal and abnormal aspects of infant feeding during the lactation period.Method: Integrative review (2024–2025) in the BVS (VHL), SciELO, and Cochrane databases, using DeCS terms “Infant,” “Mothers,” “Infant Nutrition,” and “Child Guidance,” with Boolean operators and the following criteria: original studies, full text, Portuguese/English, last 5 years. Twenty-three articles were selected. Results: Knowledge levels varied and practical gaps were identified (e.g., preparing purees/porridges), associated with education, income, and exposure to counseling. In some contexts, EBF showed high interruption rates and a short median duration; factors such as pacifier use, absence of BF in the first hour, and maternal employment were associated with weaning. Diet quality (MDD/MAD—Minimum Dietary Diversity/Minimum Acceptable Diet) was heterogeneous: community, digital (voice/text messages, apps), and primary health care (counseling with telephone follow-up) interventions increased knowledge, attitudes, and self-efficacy and reduced intake of ultra-processed foods/sugars; effects on growth were sometimes limited in the short term. In preterm infants, CF timing requires individualized guidance. Conclusions: Multimodal, continuous, culturally adapted interventions—integrating primary health care, digital strategies, and community resources—enhance maternal counseling and promote appropriate feeding practices. Structural challenges persist; longitudinal reinforcement, family/social support, and specific protocols are recommended for vulnerable contexts and preterm infants.